2016
DOI: 10.3390/nu8100662
|View full text |Cite
|
Sign up to set email alerts
|

Association between Low Dietary Protein Intake and Geriatric Nutrition Risk Index in Patients with Chronic Kidney Disease: A Retrospective Single-Center Cohort Study

Abstract: Reduced dietary protein intake in malnourished patients with chronic kidney disease (CKD) may be associated with adverse clinical outcomes, which may mask any efficacy of a low-protein diet. The study included 126 patients with CKD who attended a dedicated dietary counseling clinic in 2005–2009 and were systematically followed until January 2015. Of these patients, 20 (15.9%) had moderate or severe nutrition-related risk of geriatric nutritional risk index (GNRI) < 92; these patients were more likely to be old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
1
14
0
4
Order By: Relevance
“…Lee et al revealed that a worsening or stationary GNRI was independently associated with higher risk for major adverse cardiac and cerebrovascular events (MACCEs) in PD patients by multivariate cox analysis [48]. And reduced GNRI was also significantly associated with mortality and cardiovascular events in CKD patients not on dialysis treatment [40]. Our results have strengthened the above conclusion.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Lee et al revealed that a worsening or stationary GNRI was independently associated with higher risk for major adverse cardiac and cerebrovascular events (MACCEs) in PD patients by multivariate cox analysis [48]. And reduced GNRI was also significantly associated with mortality and cardiovascular events in CKD patients not on dialysis treatment [40]. Our results have strengthened the above conclusion.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, they also found that lowmiddle GNRI have the highest mortality rate (HR 4.28, 95%CI 2.66 to 6.88) if patients with low phosphorus level [38]. The association between GNRI and mortality has been further validated from PD and nondialysis CKD patients [39,40]. Based on all the available studies, our meta-analysis further confirmed the results that high GNRI score can decrease the risk of all-cause mortality, while low GNRI was associated with high mortality for dialysis patients.…”
Section: Discussionmentioning
confidence: 94%
“…The renoprotective effects of LPD have been demonstrated in animal models of DN (7,14) ; further, positive results with use of LPD have been reported from several clinical trials on patients with DN (44,45) . However, the results from human studies have not been consistent in different experimental settings (6,9,46) . Protein overload activates the RAS, and LPD + KA has been shown to inhibit the intrarenal RAS (47) .…”
Section: Discussionmentioning
confidence: 96%
“…In general, reduced protein intake, limited sodium and potassium intake, and reduced phosphorus intake in patients with CKD are emphasized. However, there is still controversy as to the relative advantages and disadvantages of limiting protein intake to prevent the progression of CKD without causing protein energy wasting [12]. Nutritional therapy, which can prevent the deterioration of kidney function in patients with DMCKD, and even better control of blood sugar, blood pressure, and lipid profile, are also very important [13].…”
Section: Discussionmentioning
confidence: 99%